Development and evaluation of a community of practice to improve stem cell donor recruitment in Canada. Issue 4 (2nd November 2021) - Kum, Elena; Jagelaviciute, Gabriele; Chen, Angela C.; Baharmand, Iman; Rihani, Samer; Rumball, Gabriella; Patel, Div; Kandel, Rana; Okonofua, Sylvia; Li, Edward W.; Hrycyshyn, Adriyan; Chan, Sze Wah Samuel; et al.
Abstract: Background and Objectives: Communities of practice (CoPs) represent effective models to achieve quality outcomes in health care. We report the development and evaluation of a CoP to improve stem cell donor recruitment in Canada. Materials and Methods: In September 2017, we invited national stakeholders in stem cell donor recruitment to participate in a Facebook group and regular e‐meetings. E‐meetings involved speakers and roundtable discussion on topics related to donor recruitment. The Facebook group facilitated sharing of resources. We evaluated stakeholder perspective of the CoP and the impact on recruitment outcomes. Results: As of December 2020, the CoP included 382 members who published 243 posts to the Facebook group about patient/donor stories (40%), resources (27%), updates/questions (21%) and recruitment outcomes (12%). In January 2020, we surveyed 44 CoP participants; the majority felt that the Facebook group (86%) and e‐meetings (59%) supported the community, and that the CoP fostered collaboration (82%), improved their donor recruitment knowledge (75%) and practice (77%) and improved their ability to recruit needed donors (64%). The launch of the CoP correlated with improved donor recruitment outcomes. In 2016–2017, CoP participants recruited 2918 registrants (46% male; 55.9% non‐Caucasian) compared to 4531 registrants in 2018–2019 (52.9% male; 62.7% non‐Caucasian). Members of the CoP developed innovative resources to support recruitment efforts and led national campaigns securing coverage in major media outlets. Conclusion: We describe the first CoP in stem cell donor recruitment to be formally evaluated. The CoP model may be adopted by donor recruitment organisations, registries and blood banks worldwide to improve recruitment outcomes. Highlights: A community of practice (CoP) in stem cell donor recruitment was valued by participants and supported efforts to improve recruitment outcomes. The CoP model may be adopted by donor recruitment organizations, donor registries, and blood banks worldwide to improve recruitment outcomes.